The ontogenetic growth of Anhangueridae (Pterosauria, Pterodactyloidea) premaxillary crests as revealed by a crestless Anhanguera specimen. Issue 1 (30th June 2022) - Duque, Rudah Ruano C.; Pinheiro, Felipe L.; Barreto, Alcina Magnólia Franca
ABSTRACT: The Anhangueridae are a clade of toothed pterodactyloid pterosaurs, known from their characteristic anteriorly expanded premaxillae and conspicuous rostral sagittal premaxillary and dentary crests. Most known anhanguerids come from the Lower Cretaceous Romualdo Formation within the Araripe Basin of northeast Brazil. With four currently valid genera and several specimens referred to the clade, anhanguerids are the most abundant and diverse tetrapod group in the Romualdo Formation. However, some studies suggest this diversity may be overestimated, as many taxa have been diagnosed based on subtle differences in their premaxillary crests, a structure argued to be either ontogenetically variable or sexually dimorphic. Here we describe an anterior fragment of a gracile pterosaur rostrum that possesses the single diagnostic feature of Anhanguera (fifth and sixth pairs of dental alveoli smaller than the fourth and seventh), but lacks a sagittal crest. The affinities of the new fossil among other toothed pterosaurs were tested through both cladistic and geometric morphometric approaches, which allow referral of the new specimen to Anhanguera . The absence of a crest in the new specimen of Anhanguera suggests that this structure varies in terms of ontogeny and/or sex, and that perhaps it was influenced by sexual selection.